Breast milk leptin and adiponectin in relation to infant body composition up to 2 years. Issue 1 (14th April 2014) - Brunner, S.; Schmid, D.; Zang, K.; Much, D.; Knoeferl, B.; Kratzsch, J.; Amann‐Gassner, U.; Bader, B. L.; Hauner, H.
Summary Background Adipokines in breast milk have been associated with infant growth trajectories. Objective We aimed to explore the relationship of leptin and adiponectin in breast milk with infant weight gain and body composition up to the age of 2 years. Methods Breast milk samples were collected from exclusively or partially breastfeeding mothers at 6 weeks (n = 152) and 4 months (n = 120) post‐partum. Leptin and adiponectin were determined in skim breast milk and related to infant growth and fat mass assessed by skin‐fold thickness measurements. A total of 118 infants were examined at 2 years. Results The levels of both milk adipokines were slightly lower at 4 months compared with 6 weeks post‐partum. Breast milk leptin was largely unrelated to infant anthropometric measures up to 2 years. Milk adiponectin tended to be inversely related to early infant anthropometry up to 4 months, but beyond was positively associated with weight gain and the sum of skin‐folds up to 2 years. Conclusions Our results suggest that higher adiponectin levels in breast milk might be associated with greater weight gain and higher fat mass in the offspring up to 2 years.